Curicaberis, a new genus of Sparassidae from North and Central America (Araneae, Sparassidae, Sparassinae) - Rheims, Cristina A. (Zootaxa, 2015)
The genus Curicaberis gen. nov. is described to include the type species, Curicaberis ferrugineus (C.L. Koch, 1836) comb. nov., and eight other species transferred from Olios Walckenaer, 1837: C. abnormis (Keyserling, 1884) comb. nov., C. annulatus (F.O. Pickard-Cambridge, 1900) comb. nov., C. bibranchiatus (Fox, 1937) comb. nov., C. ensiger (F.O. Pickard-Cambridge, 1900) comb. nov., C. ferrugineus (C.L. Koch, 1836) comb. nov., C. luctuosus (Banks, 1898) comb. nov., C. minax (O. Pickard-Cambridge,1896) comb. nov., C. manifestus (O. Pickard-Cambridge, 1890) comb. nov., and C. peninsulanus (Banks, 1898) comb. nov.. All species are redescribed and illustrated. The males of C. ferrugineus comb. nov. and C. luctuosus comb. nov., and the female of C. annulatus comb. nov. are described and illustrated for the first time. Twenty-three new species are described: C. azul sp. nov. (♂) from Veracruz, C. catarinas sp. nov. (♀) from Chihuahua, C. chamela sp. nov. (♂ and ♀), C. eberhardi sp. nov. (♂ and ♀), C. jalisco sp. nov. (♂ and ♀), and C. urquizai sp. nov. (♂ and ♀) from Jalisco, C. culiacan sp. nov. (♂) from Sinaloa, C. cuyutlan sp. nov. (♂) from Colima, C. durango sp. nov. (♂) from Durango, C. elpunto sp. nov. (♂ and ♀), C. sanpedrito sp. nov. (♂ and ♀), C. tortugero sp. nov. (♀), C. yerba sp. nov. (♀) and C. zapotec sp. nov. (♂) from Oaxaca, C. huitiupan sp. nov. (♂), from Chiapas, C. pedregal sp. nov. (♂) from Distrito Federal, C. potosi sp. nov. (♀) from San Luis Potosí, C. puebla sp. nov. (♀) from Puebla, C. tepic sp. nov. (♀) from Nayarit, and C. mitla sp. nov. (♂ and ♀) from Veracruz and Oaxaca, C. chiapas sp. nov. (♂ and ♀) from Chiapas and Tabasco, all in Mexico, C. granada sp. nov. (♂ and ♀) from Granada and Manágua in Nicaragua and Guanacaste in Costa Rica, and C. bagaces sp. nov. (♀), from Guanacaste, Costa Rica. An identification key and distribution maps are provided for all known species.